Chirurgická úprava virilizovaného genitálu u dievcat s kongenitálnou adrenálnou hyperpláziou - Geryk, B; Misíková, Z; Bibza, J; Strnová, J; Kubíková, E; Pribilincová, Z (Rozhledy v chirurgii, 1997)
Based on an analysis of 10 patients after a feminizing operation of a virilized genital in female pseudohermaphroditism caused by congenital adrenal hyperplasia on account of 21-hydroxylase deficiency the authors emphasize in conjunction with multidisciplinary collaboration the necessity of early modification and surgical repair with adjustment of the external genital before the age of two years. An excellent anatomical and cosmetic result of reconstruction with clitoroplasty emphasizes the importance of preserving the clitoris and erectile tissue to ensure adequate social, psychic and sexual development of the patient.
Keywords: ženské pohlavní orgány; Child, Preschool; poruchy sexuálního vývoje; Disorders of Sex Development; ženské pohlaví; Adrenal Hyperplasia, Congenital; předškolní dítě; Humans; zákroky plastické chirurgie; Female; Plastic Surgery Procedures; kongenitální adrenální hyperplazie; lidé; dítě; Genitalia, Female; Child